Occupational Stress among Psychiatric Nurses: A Literature Review - Shahd Alaween; Abdulkarim Alzayyat; Mohammad Odah (Jordan University of Science and Technology, 2024)
Background:  Occupational stress among psychiatric nurses is a well-documented issue in the literature. This research can be regarded as a first recent investigation that offered a comprehensive review of contemporary literature that examined occupational stress amongst mental health nurses. Purpose: This study aims to analyze previous research on the area of occupational stress among psychiatric nurses. Methods: Multiple electronic databases were selected as follows: PubMed, MEDLINE, PsycINFO, CINAHL. Proquest, Scopus, and Web of Science.  The researcher used different combinations of keywords that mainly incorporate: occupational stress, psychiatric nurses, and work environment". The studies included if they were published between 2017-2023 and reported in English. This review included a total of twenty five studies. Results: This review indicated that previous studies have identified various degrees and factors of stress that impact psychiatric nurses. Those psychiatric nurses utilized a number of coping methods to handle occupational stress such as being confident about self capabilities and self-assurance. The previous literature also investigated the effects of several stress reduction interventions like educational intervention, mindfulness therapy, stress management training program, and self-care activities. Conclusion: This literature review highlights the significant levels and sources of stress experienced by psychiatric nursing group. By analyzing research published in different databases about occupational stress, this review provides a comprehensive overview of contemporary findings on the topic. Implications for Nursing: Identification of various levels and sources of stress highlights the need for targeted interventions tailored to the unique stressors experienced by psychiatric nurses.